Experimental investigation of two-side heat transfer in spacer-filled channels. (August 2020) - Ciofalo, M; Cacciatore, F; Di Liberto, M; Tamburini, A
Abstract: In Membrane Distillation (MD), spacers support the membranes and promote mixing, thus reducing temperature polarization. Their efficient design requires a knowledge of the distribution of the local heat transfer coefficient h and of its dependence on Reynolds number, spacer geometry and flow-spacer relative orientation. In previous work, we applied Thermochromic Liquid Crystals (TLC) and digital image processing to the measurement of h distributions for different spacer configurations; data were used to validate CFD simulations and select turbulence models. For constructive reasons, the test section allowed only one-side heat transfer, while in most MD configurations (e.g. spiral-wound modules) heat transfer occurs from both sides of the feed water channels. Analytical and numerical solutions show that changing from one-side to two-side heat transfer deeply affects h values. This motivated the design and construction of an improved test section in which a hot channel is sandwiched between two cold channels, and twin cameras and lighting equipment allow the simultaneous acquisition of TLC images on both walls. This paper describes this new test section and the experimental technique, discusses measurement uncertainty, and presents preliminary results.